Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1744-9987.2009.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Liver Support Therapy With Prometheus in Patients With Liver Failure in the Intensive Care Unit

Abstract: Acute liver failure (ALF) and acute-on-chronic liver failure (AoCLF) are associated with a high mortality. In these patients an accumulation of both water-soluble and water-insoluble, protein-bound, metabolic waste products occurs. Conventional extracorporeal blood purification techniques based on diffusion and/or convection such as hemodialysis or hemofiltration may only eliminate small molecular weight, water-soluble compounds. In recent years, fractionated plasma separation and adsorption (FPSA) with the Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
(42 reference statements)
1
24
0
1
Order By: Relevance
“…Likewise, Oppert et al [4] observed global survival rate of 26% in patients with ALF and AoCLF submitted to Prometheus, with a higher survival rate among ALF patients. These data could not be reproduced in the present study; we did not find any difference in 6-month survival for patients who underwent LT and those who did not undergo LT.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Oppert et al [4] observed global survival rate of 26% in patients with ALF and AoCLF submitted to Prometheus, with a higher survival rate among ALF patients. These data could not be reproduced in the present study; we did not find any difference in 6-month survival for patients who underwent LT and those who did not undergo LT.…”
Section: Discussionmentioning
confidence: 99%
“…According to several authors, the serum albumin concentration during MARS-therapy remains unchanged because the diameter of the filter pores (50 kDa) does not exceed the size of the albumin molecule (65 kDa). [26,38] However, the albumin loss during Prometheus-therapy can reach 3 g/L (P = 0.055). [31,39] We observed no significant negative dynamics of serum albumin [oscillations: 32 (30-35) and 30 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) g/L, P = 0.052, before and after MARS-therapy; 33 (31-34) and 31 (28-36) g/L, P = 0.051, before and after Prometheus-therapy], which is probably due to the adequate routine correction of hypoproteinemia in patients with ALF.…”
Section: Extracorporeal Blood Purification In Intensive Care Patientsmentioning
confidence: 99%
“…This technique is the most effective for eliminating albumin-bound toxins such as unconjugated bilirubin and bile acids. [37,38] In assessing the safety and efficacy of MARS and Prometheus therapies in adult patients with ALF after cardiac surgery, we analyzed the dynamics of hydrophobic and hydrophilic toxic substance concentrations as well as the severity of hepatocyte cytolysis and the impairment of liver synthetic function. A key aspect in the evaluation of MARS and Prometheus liver support system safety in patients after cardiac surgery was the absence of a negative influence on hemodynamics and lung oxygenation function.…”
Section: Extracorporeal Blood Purification In Intensive Care Patientsmentioning
confidence: 99%
“…such as MARS5 [38] or Prometheus5 [39] where adsorbent materials do not come into direct contact with patient blood and, therefore, mitigate issues of blood cell activation and hemocompatibility.…”
Section: Cytokine Markers Removal Efficiency Of Gnp-ptfe Filmmentioning
confidence: 99%